PENDIDIKAN KARAKTER SISWA SEKOLAH DASAR, MELALUI MATA PELAJARAN PENDIDIKAN KEWARGANEGARAAN - Nuraida Nuraida (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
Character education is important because it is considered capable of creating intelligent, noble, and responsible learners who contribute both to their own community and the wider society. Civic Education taught at every school level includes teaching good morals and manners. In fact, character education in Indonesia is considered still far from the goal of forming virtuous and virtuous human beings. Innovation in the teaching and learning process is needed to address this, especially when it comes to civic education. A literature technique was used to collect data for this scientific paper. It is clear from the findings and debates that.